2014
DOI: 10.1111/jocn.12542
|View full text |Cite
|
Sign up to set email alerts
|

Physical and sexual intimate partner violence, women's health and children's behavioural functioning: entry analysis of a seven‐year prospective study

Abstract: Findings for the mental health functioning of women participating in this study add to the overwhelming evidence for the importance of screening for partner violence when women present for health care and for the need for effective assistance services for women who have or are currently experiencing partner violence. They also support emerging research that indicates the great need to provide effective services for the children of abused women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…Although it has been reported that severity of abuse affects women's mental health functioning (Campbell et al, ; Straus et al, ), in this study, we identified the specific aspects of mental health that were affected, including major symptoms of depression, anxiety, somatization, and PTSD. These findings contribute to previous evidence of correlations among maternal abuse, mental health, and child behavioral functioning (Chemtob et al, ; Emery, ; Panuzio et al, ; Spiller et al, ) by pinpointing specific mental health symptoms and expanding on the initial analyses of Symes et al () of the association between types of abuse and maternal and child well‐being at baseline in this sample.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Although it has been reported that severity of abuse affects women's mental health functioning (Campbell et al, ; Straus et al, ), in this study, we identified the specific aspects of mental health that were affected, including major symptoms of depression, anxiety, somatization, and PTSD. These findings contribute to previous evidence of correlations among maternal abuse, mental health, and child behavioral functioning (Chemtob et al, ; Emery, ; Panuzio et al, ; Spiller et al, ) by pinpointing specific mental health symptoms and expanding on the initial analyses of Symes et al () of the association between types of abuse and maternal and child well‐being at baseline in this sample.…”
Section: Discussionsupporting
confidence: 77%
“…Further, the effects of partner abuse are intergenerational (Cesario, Nava, Bianchi, McFarlane, & Maddoux, ; Hulette, Kaehler, & Freyd, ) in that maternal abuse is associated with child behavioral dysfunction (Chemtob, Griffing, Tullberg, Roberts, & Ellis, ; Emery, ; Panuzio, Taft, Black, Koenen, & Murphy, ; Spiller, Jouriles, McDonald, & Skoop, ; Symes, Maddoux, McFarlane, Nava, & Gilroy, ). Several researchers have shown that children's witnessing of their mothers’ abuse places them at risk for behavioral dysfunction (Carpenter & Stacks, ; Graham‐Bermann, Gruber, Howell, & Girz, ; Levendosky, Bogat, & Martinez‐Torteva, ; McFarlane et al, ).…”
mentioning
confidence: 99%
“…Research reveals that women with a history of adverse childhood events (e.g. sexual abuse) are at a higher risk for multiple adverse health outcomes, including higher levels of somatization and PTSD scores (Campbell, 2002;Symes, Maddoux, McFarlane, Nava, & Gilroy, 2014). Childhood experience is also a contributing factor to re-victimization (Campbell, 2002).…”
Section: Abuse and Childhood Abusementioning
confidence: 97%
“…The authors problematize conceptualizations of children as secondary or passive victims because children are directly affected, sometimes directly involved, and often active agents in resisting control. Others have found links between exposure to sexual coercion and violence against mothers and child maladjustment (Spiller, Jouriles, McDonald, & Skopp, ; Symes, Maddoux, McFarlane, Nava, & Gilroy, ). Jouriles, McDonald, Vu, and Sargent () found that sexual coercion experienced by mothers was associated with greater mother and child reports of externalizing problems.…”
Section: Individual and Relational Contextsmentioning
confidence: 99%